História, mulher e política: uma análise sobre mulheres de Concórdia do Pará e seus lugares de fala e poder nos processos eleitorais - OLIVEIRA, Dilane Cavalcante de (2022)
The objective of this article is to analyze, through the testimonies of political women, which structural and cultural mechanisms permeate political spaces and what were the difficulties of insertion and their permanence in the legislative spaces occupied in the municipal council of Concórdia do Pará. The study of this research presents the advances of female occupation in legislative spaces, its challenges and experiences linked to the social constructions that encouraged the desire for the dispute of elective positions since the territorial emancipation of the municipality in 1988. For this, dialogue with made with authors such as Michelle Perrot (2019), Margareth Rago (1995), Joan W. Scott (1995) and Simone Beauvoir (1967), to double the impact of this research as a research on gender and politics entered Luis F. Miguel (2014), Flávia Biroli (2014) and Dphane Patai (2010) to articulate history to life processes and political making and in the same way, oral history as a source of results in social and cultural groups, which dialogued with authors and studies from the area as well as historical sources, such as Marieta by M. Ferreira (2018), Carla B. Pinsky (2018), Hebe Mattos (2016), Brenda Oliveira (2017). As a result, I observe that there are many difficulties and challenges that result in a low rate of women to the elected positions held, as well as a sexist, misogynist and patriarchal social construction that makes it difficult to achieve equity in the occupations of political positions. In addition, I verify that through political education in teaching it is possible to carry out a transformation of historical knowledge for a deconstruction of the image of inferiority reflected in women and their competences for electoral disputes and the occupation of legislative positions.